Nutritional and Chemotherapeutic Management Strategies of Powdery Mildew in Pumpkin - Ali, Mubasher; Hussain, Muhammad; Mohsin Raza, M.; Khan, Rana Muhammad Muzzamal; Hussain, Waqas; Saleem, Danish; Abdussamee, Hafiz (International Journal of Bio-resource and Stress Management, 2014)
Several disease management strategies adopted by researcher that based on host resistance, chemicals and nutrient supplements. These measurements were effective for reducing the disease caused by Sphaerotheca fuliginea. Some measures were easily recommended but less easily applied. The effective use of fungicides and nutrient supplements requires the knowledge of epidemiology of disease. Powdery mildew reduces the economic gains, so the aim of integrated disease management is to reduce the economic loss. Crop protection is increasingly dependent on chemical pesticides that may cause environmental hazards. Integrated management may helps to avoid such problem. Integrated management of pumpkin powdery mildew is an environment suitable strategy, which seeks to minimize the use of chemical by placing more reliance on other non-chemical methods like nutritional management. The ultimate objective of the management strategy is to produce the optimum crop yield of high quality at minimum cost and the long-term goal is to reduce the environmental hazards by less dependence on chemical control measures.